Mimosa pigra in eastern and southern Africa: Distribution and socio‐ecological impacts. (10th May 2020) - Witt, Arne B.R.; Floyd, Kelvin S.; Nunda, Winnie; Beale, Tim; Shanungu, Griffin; Kriticos, Darren J.
Abstract: The semiaquatic weed Mimosa pigra has negative impacts on biodiversity, fishing, crop and livestock production, and tourism in most places where it has been introduced, established and proliferated. Many of the ecological impacts are well known, but its impacts on rural livelihoods are less well documented, especially in Africa. We mapped the distribution of M. pigra in eastern and southern Africa, and then compared that with its potential distribution based on an ecoclimatic niche model. Household interviews were conducted to assess the impacts of this weed on local livelihoods. Mimosa pigra was found to be invasive in western Ethiopia, around the shores of Lake Victoria and Lake Tanganyika, and along the Tanzanian coastline, northern Malawi, parts of Mozambique and along the Kafue River and in the Barotse floodplain on the Zambezi River in Zambia. According to respondents living along the Kafue River floodplains in Zambia, it has a negative impact on biodiversity, wildlife, livestock, crop production, fishing and mobility. Dense stands prevented the movement of people and livestock, limiting access to croplands, grazing lands and fishing areas. Fish catches have been reduced and fishing equipment damaged. All respondents agreed that their livelihood options would be considerably enhanced if M. pigra was removed from the landscape. Based on its current and potential impact, we therefore recommend that an integrated management plan be developed and implemented, including the appropriate use of biological control agents to reduce the negative impacts of the weed.